The effect of monofluorophosphate implant in white rat mothers towards the level of fluor in the incisors of their young babies (Rattus-rattus) - Widjijono, Widjijono (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: Fluoride has been widely used in the prevention of dental caries for a long time. To prevent dental caries, fluoride must be induced in low amount at high frequency. Inducing it through implantation process even make slow release of small concentration of fluoride. Purpose: The aim of this research was to analyze whether the induction of monofluorophosphate (MFP) implant into the white rat mothers affects the level of fluoride in the incisors of their young babies. Method: The objects of the research were twenty white rat mothers in two days of pregnancy which then were divided into four groups (n=5). First, those mothers have been induced with implant under their back skin until their born young babies in the age of 35 days (n=5). The level of fluoride in the incisors of those young babies then is measured with Potentiometer. The obtained data were finally analyzed with One-Way ANOVA test and continued by with LSD test (p=0.05). Result: The result of this research showed that the means of the fluoride level in the incisors of those babies divided into those four groups in series were about 11956.16±201.35 ppb (K), 27328.04±234.56 ppb (P1), 37267.21±248.86 ppb (P2), and 18103.50±267.11 ppb (P3). The result of ANOVA test then showed that the induction of various MFP implant levels significantly affected the level of fluoride in the incisors of the babies. The mean differences among the treatment groups after being tested with LSD 0.05 were also significant. Conclusion: The finding confirm that the significant increasing of the optimal fluoride retention in the incisors of white rat babies can be achieved with the induction of fluoride with MFP ions implant in about 52.98 mg.Latar belakang: Pencegahan karies gigi menggunakan senyawa fluor telah banyak dilakukan dan berlangsung dalam jangka waktu lama. Pemberian fluor dalam jumlah rendah dan frekuensi tinggi merupakan pemenuhan kebutuhan pencegahan karies gigi. Pemberian dengan cara implantasi memberikan keluaran fluor jumlah kecil dan waktu lama. ...